Patients' perception regarding the use of a long-term catheter - Martins, Fernanda Titareli Merizio; Carvalho, Emilia Campos de (Revista da Escola de Enfermagem da USP, 2008)
This study aimed to evaluate patients' perception regarding their use of a Totally Implanted Catheter (TIC). This descriptive study uses the Critical Incident Technique (CI) for data analysis. The study was performed at a Teaching Hospital in São Paulo State, Brazil. Study participants were 15 patients using TIC. Data were grouped into four categories: Activity Performance (40% of the CI showed that patients were more independent, while 60% revealed that some kind of activity was restricted due to the TIC); Altered Body Image (57% showed the patients' dissatisfaction after the TIC implant, 14% of the CI revealed pre-implant problems, 28% of the CI showed that the TIC favored body esthetics); Catheter Implantation (75% of the CI revealed catheter implantation as a traumatizing procedure, while 25% of the CI revealed patients remained calm and confident during the procedure); Chemotherapy Infusion (100% of the CI showed that the catheter made chemotherapy easier).